Atividade antitumoral de nitroquinona derivada da Nor-β-lapachona: contribuição da farmacoeletroquímica na pesquisa do mecanismo de ação de novos fármacos - Moura, Maria Aline Barros Fidelis de (2008)
Cancer is one of the most dreadful diseases due to its figure of morbidity and mortality and its strong social and economic impact in public healthy. The development of new chemotherapics is urgently required. Pharmoelectrochemical studies are important tools in pharmaceutical chemistry, pharmacology and biomedicine. In the present work, the cytotoxic activity of the nitroquinone 2,2–dimethyl–3-(3-nitrophenylamine)-2,3-dihydronaphtho[1,2-b]furan-4,5-dione, was performed, using electrochemical and pharmacological methods, in order to elucidate its mechanism of reduction and biological action. Additionally, electrochemical behaviour of cytotoxic arylamine and [1,2,3] triazolic naphthoquinones was investigated, in order to obtain reduction potentials, to correlate them with their biological activity. Studies were undertaken in aprotic medium (DMSO/TBAP and Acetonitrile/TBABF4) and protic medium (acetate buffer pH 4.5). The nitroquinone was further investigated, concerning its cytotoxicity, genotoxicity, cells morphological modification and immunomodulation effects in its presence, using, for that, dsDNA biosensors and flow cytometry, with the main goal of proposing its pharmacological mechanism of antitumour action. The nitroquinone is not genotoxic and it caused apoptosis, by an intrinsic (mithocondrial) pathway. The electrochemical behaviour of all the quinones, in aprotic and protic media, are typical of well-behaved quinones. The triazole ring worked as a highly electronwithdrawing group, shifting positively all the redox potentials. The nitroquinone has hybrid electrochemical behaviour due to the presence of two eletroactive groups in the molecule. The analysis by ESR allowed the definition of its reduction mechanism. Reduction potential values (EpIc) of the two sets of substances are not directly related to the pharmacological activities of the compounds. Log P values showed better correlation with the biological activity. With the aid of dsDNA biosensor, and ssDNA in a modified electrode, it was possible to analyse the positive and direct interaction of acridines with DNA. The adaptation of the methodology of ssDNA, enabling the study of these (insoluble) substances in ssDNA, demonstrated the contribution of pharmoelectrochemistry to the discovery of the mechanism of action of drugs.